4+6r-r=-5+8r

Simple and best practice solution for 4+6r-r=-5+8r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+6r-r=-5+8r equation:


Simplifying
4 + 6r + -1r = -5 + 8r

Combine like terms: 6r + -1r = 5r
4 + 5r = -5 + 8r

Solving
4 + 5r = -5 + 8r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-8r' to each side of the equation.
4 + 5r + -8r = -5 + 8r + -8r

Combine like terms: 5r + -8r = -3r
4 + -3r = -5 + 8r + -8r

Combine like terms: 8r + -8r = 0
4 + -3r = -5 + 0
4 + -3r = -5

Add '-4' to each side of the equation.
4 + -4 + -3r = -5 + -4

Combine like terms: 4 + -4 = 0
0 + -3r = -5 + -4
-3r = -5 + -4

Combine like terms: -5 + -4 = -9
-3r = -9

Divide each side by '-3'.
r = 3

Simplifying
r = 3

See similar equations:

| x+9=-17 | | 10x+x=196 | | (1/4)(p)+6=8 | | 6x+39x-7=9(5x+6) | | 4x-10=14+x | | 35=7(z)-7 | | 8(n)+16=24 | | 8.2x-2.1x=-122 | | 2(x+5)=4x+6-2x+4 | | 9x=2.25 | | -8=3(y)-2 | | 5(h)-13=12 | | 12x^3=27x^2+15x | | 6k-1-7=10 | | 7x-2=5x+8 | | 6=42-5q-q^2 | | 3x-1/(2)=10 | | -6a-5a=11 | | 3x-1/2=10 | | 2=3(a)+8 | | (3x^2+7x-20)/(x+5) | | graphy=.5x+.5 | | -8x-3x=11 | | 9x+15x-8=6(4x+5) | | -3(d)+10=43 | | t+6t+9=0 | | -2=1+6x-3x | | 25x^2-20x-19=0 | | -6b^2+1b+3=0 | | -4w+2z-5z+3w=9 | | 3x^2+64=(2X^2)/2 | | 2x+2x+2x+3+4=180 |

Equations solver categories